The influence of work motivation and work discipline on employee productivity at PT. Wahana Internet Nusantara - Ega Muhammad Hidayat; Wanta; Dwi Epty Hidayaty (LPPM STIE EKA PRASETYA, 2024)
Wahana Internet Nusantara uses a productivity-based performance measurement system with a minimum target of 90% every month. Employee productivity data in 2023 will fluctuate or be unstable, which could cause problems for the company. The aim of this research is to identify and analyze how work motivation, work discipline, and the influence of both simultaneously and partially on the work productivity of PT employees. Archipelago Internet Forum. This research uses a quantitative approach with descriptive verification. The analysis was carried out using multiple linear regression with the help of the SPSS version 26 analysis tool, and the sample was saturated, with a population of 52 people. Data was collected through questionnaires, observation and literature study. The research results show that work discipline and work motivation both have a significant positive partial effect on employee productivity, while the simultaneous influence of work motivation and work discipline has a significant positive effect on productivity. Motivated employees will be more enthusiastic in completing tasks and will always contribute to the overall success of the company. Employees who have high discipline will make important contributions that can increase company productivity